الرؤى والآفاق المستقبلية للتعليم العربي في نيجيريا - Adebayo Sirajudeen, Adam; Adeleke Adeyemi, Kamil (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Arabic has been taught in Nigeria as far back as the inception of Islam in the region. The coming of the Europeans brought the teaching of Arabic to the higher institutions of learning where the language is taught up to the doctoral level. Trove of literary works has been produced via the academic and non-academic learning of Arabic. This work examines the triumphs and travails of the Arabic teaching over the decades in Nigeria. It looks at the future prospects of Arabic as could be found in its change and continuity. The paper notes the necessity of identifying the focus of the teaching, updating curricula, contemporaneity of the teaching methodologies and research methods, etc. The paper concludes that for the Arabic teaching in Nigeria to meet up with the necessity of the contemporary requirement for development, all these items need to be adequately addressed. This was followed by suggestions and way forward.